World economic growth and seaborne trade volume: Quantifying the relationship. (March 2020) - Michail, Nektarios A.
Abstract: This article quantifies the relationship between the world macroeconomic environment and the demand for seaborne transport, using annual data on the quantity of crude oil, petroleum products and dry cargo transported. Using a Vector Error Correction Model (VECM) we capture their long-run relationship with world GDP and the price of oil, which serves as a proxy for freight rates. The results suggest that all three categories are affected by changes in the world economic environment, albeit to a different extent. Responses to a shock in the price of oil support the argument of the price inelasticity of demand. Dividing the world economy into high, middle and low income countries suggests that the first two always have a positive effect on demand, while low income countries have a negative effect. The quantification of these effects has a wide range of implications in the shipping industry ranging from freight rate forecasts and the associated implications for long-term chartering of vessels, to shipping valuations, risk management, and the mode of financing. Highlights: Examine the relationship of world macro environment and demand for sea transport. Results suggest that cargo types are affected to a different extent. Responses to oil shock support the price inelasticity of demand. High and middle income countries have a positive effect on demand. Quantification of these effects allows for better risk management practices.